Of extreme monsters and extraordinary mutations: A critical appreciation of Neal Asher’s jack four as a masterly work of body horror bildungsroman - Patra, Indrajit (Linguistics and Culture Review, 2021)
The present article seeks to analyse Neal Asher’s novel Jack Four (2021) to show how elements of posthuman monstrosity and extreme biological horror can combine to produce a unique kind of transgressive and transformative effect that radically alters the very definition of human and blurs the boundaries between human and non-human. As part of its theoretical framework, the article seeks to employ Braidotti’s idea of ‘epistemophilic’, Braidotti’s ‘Zoe’-centred view of the posthuman dimension of post-anthropocentrism, and Betterton’s (2006) idea of the boundary-problematizing potential of the monstrous ‘Other’ among many others. The article strives to show how Asher’s portrayal of extreme forms of posthuman monsters not only harnesses the near-inexhaustible transgressive power of the essentially indefinable monstrous figure but also by combining with the gruesome portrayal of endless body horror, it seems to project the human body as a site of endless becomings, connectivities and proliferations.